Does the HOTS Based Inquiry Training Learning Model Improve Children's Critical Thinking Skills in Islamic Religious Education Learning? Meta-analysis - Sari, Windy Dian; Sarnoto, Ahmad Zain; Alhan, Khusni; Widodo, Hadi; Santosa, Tomi Apra; Yastanti, Unpris (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the influence of HOTS-based inquiry training model on critical thinking skills in PAI learning meta-analysis. Research data were obtained from 26 studies that met the inclusion criteria. Research data was obtained through the databases of ERIC, ScienceDirect, Wiley, Taylor of Francis, Mendeley and IEEE. Data analysis calculates the effect size value with the help of the JASP application. The results of the study concluded that the mean effect size value after analysis was found to be d =1.150 ; p < 0.001; z = 9.273.. These findings explain that the HOTS-based inquiry training model has a positive effect on childrenÂ  critical thinking skills in PAI learning. This research provides important information in the application of this model to encourage children's critical thinking skills in learning Islam.